The Influence of the Tricyclic Antidepressant Amitriptyline on Periodic Limb Movements during Sleep - Goerke, M.; Rodenbeck, A.; Cohrs, S.; Kunz, D. (Pharmacopsychiatry, 2013)
Many antidepressants are associated with periodic limb movements (PLM) during sleep. Although some tricyclic antidepressants, such as amitriptyline, promote sleep and are thus often prescribed as a treatment for sleep disturbances that can accompany depression, it remains unclear whether amitriptyline is associated with PLM.32 healthy males (18–39 years) spent 2 consecutive nights in the sleep lab for polysomnographic recording. During the second night, they received either 75 mg amitriptyline or placebo in a randomized, double-blind, placebo-controlled manner.In subjects receiving amitriptyline but not in subjects receiving placebo, the number of periodic leg movements per h was significantly increased from baseline to intervention night. However, objective polysomnographic sleep parameters (such as the number of awakenings, wake after sleep onset, and sleep efficiency) and subjective sleep perception were not significantly associated with any PLM indices.Our findings indicate that amitriptyline can induce or even increase the number of PLM during sleep in healthy subjects. When treating sleep disturbances with amitriptyline, PLM should be considered as a possible cause of insufficient improvement.
Keywords: antidepressants; sleep disturbance; periodic limb movements